Generalized Anxiety Disorder in Very Young Children: First Case Reports on Stability and Developmental Considerations - Scheeringa, Michael S.; Burns, Lauren C. (Case Reports in Psychiatry, 2018)
Generalized anxiety disorder (GAD) is purported to start in early childhood but concerns about attenuation of anxiety symptoms over time and the development of emerging cognitive and emotional processing capabilities pose multiple challenges for accurate detection. This paper presents the first known case reports of very young children with GAD to examine these developmental challenges at the item level. Three children, five-to-six years of age, were assessed with the Diagnostic Infant and Preschool Assessment twice in a test-retest reliability study. One case appeared to show attenuation of the worries during the test-retest period based on caregiver report but not when followed over two years. The other two cases showed stability of the full complement of diagnostic criteria. The cases were useful for demonstrating that the current diagnostic criteria appear adequate for this developmental period. The challenges of accurate assessment of young children that might cause missed diagnoses are discussed. Future research on the underlying dysregulation of negative emotionality and long-term follow-ups are needed to better understand the etiology, treatment, and course of GAD in this age group.